Frequency of cardiovascular and gastrointestinal malformations, leukemia and hypothyroidism in children with Down syndrome in Trabzon, Turkey - Aynacı, F. Müjgan; Orhan, Fazıl; Celep, Figen; Karagüzel, Ahmet (The Turkish Journal of Pediatrics, 1998)
This study was carried out to determine the frequency of congenital heart defects, cholelithiasis, hypothyroidism and leukemia in 31 children with Down syndrome. Twenty children (71.4%) had congenital heart defects. Ultrasonography was performed on 29 and two of these (6.9%) had cholelithiasis. Tests for hypothyroidism in 24 children identified hypothyroidism in three (12.5%). Leukemia was diagnosed in three children (10%) (one with congenital, two acquired). One patient with congenital hypothyroidism underwent surgery on the third day of life because of annular pancreas and duodenal atresia.
Keywords: Down syndrome; congenital heart defect; hypothyroidism; cholelithiasis; annular pancreas; leukemia